Functional nanowires and nanotubes : symposium held November 28-December 2, 2011, Boston, Massachusetts, U.S.A. - Symposium BB, "Functional Nanowires and Nanotubes" (2011 : Boston, Mass.); Fontcuberta i Morral, Anna.; Materials Research Society (Warrendale, Pa. : Materials Research Society : Cambridge ; New York : Cambridge University Press, 2012)
Symposium BB, 'Functional Nanowires and Nanotubes', was held November 27-December 2 at the 2011 MRS Fall Meeting.
Part I. Optical Properties: 1. Composition and size effects on the optical properties of isolated silicon-germanium nanowires Houssem Kallel, Abdallah Chehaidar, Arnaud Arbouet, Thierry Baron, Alexis Potie, Bassem Salem and Vincent Paillard; 2. Photomodulated Rayleigh scattering from single semiconductor nanowires Mohammad Montazeri, Aaron Wade, Melodie Fickenscher, Howard E. Jackson, Leigh M. Smith, Jan M. Yarrison-Rice, Qiang Gao, H. Hoe Tan and Chennupati Jagadish; 3. Photoconductivity of ZnO nanowires decorated with CdSe quantum dots Dongchao Hou, Apurba Dev, Kristian Frank, Andreas Rosenauer and Tobias Voss; 4. Vector magneto-optical generalized ellipsometry on passivated permalloy slanted columnar thin films Daniel Schmidt, Chad Briley, Eva Schubert and Mathias Schubert; 5. Photoluminescence and Raman scattering studies of GaN nanowires obtained by top-down and bottom-up approaches Toma Stoica, Anna Haab, David Griesche, Martin Mikulics, Friederich Limbach, Timo Schumann, Tobias Gotschke, Eli Sutter, Raffaella Calarco, Hilde Hardtdegen and Detlev Grutzmacher; Part II. Electrical Transport and Energy Harvesting Devices: 6. Individualization and electrical characterization of SiGe nanowires M. Monasterio, A. Rodriguez, T. Rodriguez and C. Ballesteros; 7. Carrier transport in GaAs nanowires using surface acoustic waves A. Hernandez-Minguez, M. Moller, C. Pfuller, S. Breuer, O. Brandt, M. M. de Lima, A. Garcia-Cristobal, A. Cantarero, L. Geelhaar, H. Riechert and P. V. Santos; 8. Synthesis of Si nanowires by electroless etching technique and their integration into I-III-VI2 thin films for solar cells H. Karaagac, M. Parlak and M. Saif Islam; 9. SiGe nanowires grown by LPCVD using Ga-Au catalysts M. Monasterio, A. Rodriguez, T. Rodriguez and C. Ballesteros; 10. Thermoelectric properties of silicon nanowire array and spin-on glass composites fabricated with CMOS-compatible techniques Benjamin M. Curtin and John E. Bowers; 11. Thermoelectric properties of p and n-type nanocrystalline silicon nanowires with high doping levels F. Suriano, M. Ferri, S. Solmi, L. Belsito, A. Roncaglia, E. Romano, D. Narducci and G. Cerofolini; 12. Fabrication of SrTiO3 nanofibers for hydrogen production Lea Macaraig, Surawut Chuangchote and Takashi Sagawa; Part III. Growth of Nanowires and Novel Structures: 13. Kinetics and statistics of vapor-liquid-solid growth of III-V nanowires Jean-Christophe Harmand, Frank Glas, Gilles Patriarche, Fauzia Jabeen and Mohamed Reda Ramdani; 14. Pathway of porous silicon formation inside Si nanowires throughout metal assisted etching Alexander A. Tonkikh, Nadine Geyer, Bodo Fuhrmann, Hartmut S. Leipner and Peter Werner; 15. A systematic study of metal-assisted chemical etching parameters for well-ordered silicon nanowire array fabrication Arif S. Alagoz and Tansel Karabacak; 16. Characterization of magnetic transformation at Curie temperature in finemet-type microwires by DSC Sergey Kaloshkin, Margarita Churyukanova and Victor Tcherdyntsev; 17. Template assisted fabrication and magnetic properties of cobalt ferrite nanostructures Jian H. Zhang, Liyin Chen and Xylona L. Williams; 18. Synthesis and morphology control of carbon nanotube/polyaniline composite for chemical sensing Mengning Ding and Alexander Star; 19. Diffusion instability and tapering of nickel silicide intrusions in silicon nanowires Alex Katsman, Michael Beregovsky and Yuval E. Yaish; 20. Preparation of Al2O3 and AlN nanotubes by atomic layer deposition Cagla Ozgit, Fatma Kayaci, Inci Donmez, Engin Cagatay, Tamer Uyar and Necmi Biyikli; 21. Silicon nanowires obtained by low temperature plasma-based chemical vapor deposition R. A. Puglisi, G. Mannino, S. Scalese, A. La Magna and V. Privitera.
"Symposium BB, "Functional Nanowires and Nanotubes", was held November 27-December 2 at the 2011 MRS Fall Meeting in Boston, Massachusetts"--Pref.
engineering bookfair2015
Includes bibliographical references and indexes.
Keywords: Nanotubes -- Congresses; Nanowires -- Congresses